THE USE OF ALGAE CONCENTRATES, DRIED ALGAE AND ALGAL SUBSTITUTES TO FEED BIVALVES - Ludi Parwadani Aji (Makara Seri Sains, 2011)
Microalgae have high nutritional value and are used to feed adult and larval stages of bivalves, the larvae of some fish and crustaceans and zooplankton. However, microalgae production for aquaculture animal is very expensive. To overcome this, the use of preserved microalgae such as algae concentrate and dried algae, or algal substitutes has been developed. There are both advantages and disadvantages to this alternative food. For example, even though the cost production for algal substitute yeast-based diet is cheaper, their nutritional value is much lower compared to fresh microalgae. Moreover, there is no significant difference in nutritional value between preserved (concentrated or dried) and fresh microalgae; however, preserving microalgae for long periods will affect their nutritional value. In spite of this problem, preserved microalgae such as algal concentrate and dried algae seem to be more effective to feed bivalves than algal substitutes yeast based diet due to their availability and relatively high nutritional value. Furthermore, algae concentrates are more suitable to replace fresh algae than dried algae.